Book Worlds as a Window to Analyze the Extreme Right Wing in Argentina - Saferstein, Ezequiel; Goldentul, Analia (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2023)
This paper examines how certain contemporary books and authors contributed to the formation of an extreme right political option in Argentina. The paper focuses on Nicolás Márquez and Agustín Laje, two authors who have achieved unprecedented visibility, which is reflected in the circulation and sales of their books, in the number of their followers on social networks, and in the magnitude of their events and conferences. In 2016, the publication of El libro negro de la nueva izquierda. Ideología de género o subversión cultural [The Black Book of the New Left: Gender Ideology or Cultural Subversion] established both authors as figures with “authority” in right-wing culture, and enabled the formation of communities of young readers from the promotional circuit of the work. Having attended different events and conducted a series of in‑depth interviews with young readers, we explore the forms of sociability and political subjectivation enabled by these authors and this book in the space of circulation of right-wing ideas in Argentina today.